2019
DOI: 10.1155/2019/4946181
|View full text |Cite
|
Sign up to set email alerts
|

miR-98-5p Alleviated Epithelial-to-Mesenchymal Transition and Renal Fibrosis via Targeting Hmga2 in Diabetic Nephropathy

Abstract: Recently, microRNAs have been recognized as crucial regulators of diabetic nephropathy (DN) development. Epithelial-to-mesenchymal transition (EMT) can play a significant role in tubulointerstitial fibrosis, and it is a hallmark of diabetic nephropathy progression. Nevertheless, the function of miR-98-5p in the modulation of EMT and renal fibrosis during DN remains barely investigated. Hence, identifying the mechanisms of miR-98-5p in regulating EMT and fibrosis is of huge significance. In our present research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 36 publications
1
22
0
Order By: Relevance
“…As well known, EMT is a kind of biological course, and epithelial cells can transdifferentiate into mesenchymal cells in this process and is able to contribute to pathological fibrosis. 49 Interestingly, activation of both MAPKs and SMAD2/3 has been reported to be involved in the process of EMT. 50,51 In EMT process, transcription factor snail1 activated by high glucose would inhibit the transcription and production of epithelial marker ZO-1, epithelial cells activate, and then, transdifferentiate to mesenchymal cells, followed by the elevating expression of mesenchymal marker α-SMA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As well known, EMT is a kind of biological course, and epithelial cells can transdifferentiate into mesenchymal cells in this process and is able to contribute to pathological fibrosis. 49 Interestingly, activation of both MAPKs and SMAD2/3 has been reported to be involved in the process of EMT. 50,51 In EMT process, transcription factor snail1 activated by high glucose would inhibit the transcription and production of epithelial marker ZO-1, epithelial cells activate, and then, transdifferentiate to mesenchymal cells, followed by the elevating expression of mesenchymal marker α-SMA.…”
Section: Discussionmentioning
confidence: 99%
“…As well known, EMT is a kind of biological course, and epithelial cells can transdifferentiate into mesenchymal cells in this process and is able to contribute to pathological fibrosis 49 . Interestingly, activation of both MAPKs and SMAD2/3 has been reported to be involved in the process of EMT 50,51 .…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, some miRNAs exert protective effects by inhibiting the epithelial-to-mesenchymal transition (EMT). Notably, miR-30c, miR-98-5p and miR-302a-3p target the fibrosis-related JAK1, Snail1, HMGA2, and ZEB1, respectively, thus blocking the fibrotic process in DKD by inhibiting EMT ( Zhao et al, 2017 ; Tang et al, 2018b ; Zhu et al, 2019c ; Gao et al, 2020 ). Furthermore, miR-455-3p also inhibits renal fibrosis by targeting ROCK2, together with the reduction of anti-inflammatory cytokines such as tumor necrosis factor-α (TNF-α) and monocyte chemotactic protein 1 (MCP-1) ( Wu et al, 2018a ).…”
Section: The Emerging Role Of Non-coding Rnas In Dkdmentioning
confidence: 99%
“…High mobility group AT-hook 2 (HMGA2), a small non-histone protein of the HMGA family, is an important regulator in EMT of development and neoplasia process ( Fusco and Fedele, 2007 ; Fedele and Fusco, 2010 ; Macrì et al , 2016 ). More notably, HMGA2 has been implicated in EMT processes in some fibrotic diseases ( Wang et al , 2016a , b ; Hou et al , 2018 ; Zhu et al , 2019 ). Studies have reported that regulating HMGA2 expression prevented renal fibrogenesis and that loss of HMGA2 weakened EMT in tubular epithelial cells ( Wang et al , 2016a , b ; Zhu et al , 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…More notably, HMGA2 has been implicated in EMT processes in some fibrotic diseases ( Wang et al , 2016a , b ; Hou et al , 2018 ; Zhu et al , 2019 ). Studies have reported that regulating HMGA2 expression prevented renal fibrogenesis and that loss of HMGA2 weakened EMT in tubular epithelial cells ( Wang et al , 2016a , b ; Zhu et al , 2019 ). In addition, HMGA2 was also involved in EMT of pulmonary fibrosis and lens fibrosis through transforming growth factor (TGF)-β signaling pathways ( Wang et al , 2016a , b ; Hou et al , 2018 ).…”
Section: Introductionmentioning
confidence: 99%